The Impact of Emotional Intelligence on Conditions of Trust among Leaders at the Kentucky Department for Public Health - Knight, Jennifer Redmond; Bush, Heather M.; Mase, William A.; Riddell, Martha Cornwell; Liu, Meng; Holsinger, James W. (Frontiers in Public Health, 2015)
There has been limited leadership research on emotional intelligence and trust in governmental public health settings. The purpose of this study was to identify and seek to understand the relationship between trust and elements of emotional intelligence, including stress management, at the Kentucky Department for Public Health. The Kentucky Department for Public Health (KDPH) serves as Kentucky’s state governmental health department. KDPH is led by a Commissioner and composed of seven primary divisions and 25 branches within those divisions. The study was a non-randomized cross-sectional study utilizing electronic surveys that evaluated conditions of trust among staff members and emotional intelligence among supervisors. Pearson correlation coefficients and corresponding p-values are presented to provide the association between emotional intelligence scales and the conditions of trust. Significant positive correlations were observed between supervisors' stress management and the staff members' trust or perception of supervisors' loyalty(r=0.6, p=0.01), integrity(r=0.5, p=0.03), receptivity(r=0.6, p=0.02), promise fulfillment(r=0.6, p=0.02) and availability (r=0.5, p=0.07). This research lays the foundation for emotional intelligence and trust research and leadership training in other governmental public health settings, such as local, other state, national or international organizations. This original research provides metrics to assess the public health workforce with attention to organizational management and leadership constructs. The survey tools could be used in other governmental public health settings in order to develop tailored training opportunities related to emotional intelligence and trust organizations.